Identify the most prevalent behavioral problems among orphaned children from the point of view of supervisors in the light of some variables in the center of child care in Muscat Governorate - Al Attar, Yousef Mohammed Abdullah (Journal of Educational and Psychological Sciences, 2019)
The aim of this study was to identify the most prevalent behavioral problems among orphaned children from the point of view of supervisors in the light of some variables in the center of child care in Muscat Governorate, and the number of the sample (44) supervisor and supervisor. The researcher used the measure of behavioral problems in children deprived of the family environment by the preparation of Hoywa (2016). The research followed the descriptive approach, and the research found that the most common behavioral problems in orphaned children is the problem of lying and then the problem of hyperactivity followed by the problem of aggressive behavior and in the latter came the problem of aggressive behavior. The study also showed no statistically significant differences between males and females in behavioral problems.
Keywords: behavioral problems; orphaned children; Child Care Center; maskat city